2020
DOI: 10.1101/2020.04.09.034009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic Analysis of Bacterial Community Associated with Rhizosphere and Phyllosphere of Basmati Rice

Abstract: 17 Rice is one of the most important crops for feeding about more than half of the world's 18 population. Yield of rice crop is significantly hampered by various biotic and abiotic 19 factors. Application of cost-effective and environment-friendly bioinoculant is a 20 common practice to combat the yield losses of rice in this era. The rhizosphere and 21 phyllosphere of rice plants provide specific habitats for various micro-organisms. In the 22 present study, the bacterial population dwelling the rhizosphere a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Interestingly, the population of bacteria in rice rhizosphere was explored metagenomically. In 2020, the population of bacteria in the rhizosphere and phyllosphere of Basmati rice was reported [ 197 ]. Bacterial population associated with the rice rhizosphere from three different rice growing areas (Faisalabad, Gujranwala, and Sheikhupura) of Punjab, Pakistan, were compared.…”
Section: The Pgpb As Biocontrol Agentmentioning
confidence: 99%
“…Interestingly, the population of bacteria in rice rhizosphere was explored metagenomically. In 2020, the population of bacteria in the rhizosphere and phyllosphere of Basmati rice was reported [ 197 ]. Bacterial population associated with the rice rhizosphere from three different rice growing areas (Faisalabad, Gujranwala, and Sheikhupura) of Punjab, Pakistan, were compared.…”
Section: The Pgpb As Biocontrol Agentmentioning
confidence: 99%
“…The NGS metabarcoding-based microbiome profiling revealed the predominance of phylum Proteobacteria on the rice phyllosphere. The predominance of Proteobacteria consisting of bacterial communities belonging to Enterobacteriaceae and Pseudomonadaceae is reported on the phyllosphere by many workers ( Knief et al, 2012 ; Ren et al, 2014 ; Roman-Reyna et al, 2019 ; Yasmin et al, 2020 ). At the lower taxonomic genus hierarchy, Pantoea followed by Pseudomonas and Enterobacter were overrepresented on both the rice genotypes.…”
Section: Discussionmentioning
confidence: 83%
“…mNGS-survey coupled with culturing-based validation revealed diverse bacterial ora on the phyllosphere of rice. Members belong to phyla such as Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes were found consistently on phyllosphere of both the resistant and susceptible genotypes grown Mountain and Island zones; dominance phylum -Proteobacteria on phyllosphere is reported by many workers [64][65][66]. Recently, Roman-Reyna et al [67] found region-speci c microbial hubs belonging to diverse bacterial families in rice after studying 3024 accessions.…”
Section: Discussionmentioning
confidence: 90%